Evaluation of SLC6A8 species conservation and the effect of pathogenic variants on creatine transport - Taryn Diep; Gerald S. Lipshutz (HGG Advances)
Summary: Creatine phosphate is a high-energy molecule essential for the normal functioning of highly metabolically active organs and tissues. SLC6A8 encodes the only known creatine transporter in humans (CRT1); pathogenic variants result in a neurophenotype that includes intellectual disability, seizures, and autistic-like behaviors. Due to the importance of creatine phosphate in normal brain function, we compared the amino acid sequence among a group of terrestrial mammals and zebrafish. Finding high interspecies invariance, we (1) sought to quantitatively assess the effect of a number of existing disease-causing SLC6A8 variants on in vitro creatine uptake, comparing variant type/location, along with (2) the reported effect of missense variants on severity classification. Creatine uptake in the pathogenic variants studied demonstrated that the vast majority had a profound effect on uptake; only 1, in a peripheral extracellular loop, had a moderately reduced effect. Of the missense variant analysis, those occurring in C and N termini were tolerated more, while variants in transmembrane domains tended to more likely affect function. While the high degree of amino acid conservation across terrestrial mammals underscores its evolutionary importance, together with the variant analysis, these findings provide a framework for understanding genotype-phenotype correlations in variants of CRT1 and highlight the critical functional constraints.